2023
DOI: 10.1038/s41377-023-01127-0
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite photodetector-based single pixel color camera for artificial vision

Abstract: Narrowband red, green, blue self-filtering perovskite photodetectors and a broadband white photodetector are incorporated into a single pixel imaging camera to mimic the long-, medium-, and short-wavelength cone cells and rod cells in human visual system, leading to the demonstration of high-resolution color images in diffuse mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This approach represents a promising direction for the future of photodetection, offering a balance between material excellence and manufacturing feasibility. For instance, Mai and Wang et al 100,101 have demonstrated the potential of perovskite-based SPI by using three distinct perovskite types, each sensitive to red, green, or blue light. When combined with the Fourier imaging algorithm for SPI, they effectively generated color images from monochromatic data, especially when the RGB photodetectors are exposed to low light levels at 20 μW cm −2 .…”
Section: Spectral Breakthrough By Perovskitementioning
confidence: 99%
“…This approach represents a promising direction for the future of photodetection, offering a balance between material excellence and manufacturing feasibility. For instance, Mai and Wang et al 100,101 have demonstrated the potential of perovskite-based SPI by using three distinct perovskite types, each sensitive to red, green, or blue light. When combined with the Fourier imaging algorithm for SPI, they effectively generated color images from monochromatic data, especially when the RGB photodetectors are exposed to low light levels at 20 μW cm −2 .…”
Section: Spectral Breakthrough By Perovskitementioning
confidence: 99%
“…In the field of modern technology, photodetectors play a key role, and their main function is to convert information-carrying optical signals into electronic signals for further processing and application in electronic devices. 1–3 This technology is widely used in the fields of image processing, 4,5 optical communication, 6,7 etc. , and has a profound impact on our daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Photodetectors (PDs) are widely employed in a diverse array of technology platforms including chemical analysis, 1 medicine, 2 4 environmental monitoring, 5 , 6 defense, 7 , 8 imaging, 9 , 10 space exploration, 11 communications, 12 14 and the Internet of things. 15 , 16 Recently, metal halide perovskites have attracted massive interest owing to their high optical absorption coefficients of >10 4 cm –1 , long charge carrier lifetimes of >1 μs, diffusion lengths exceeding 1 μm, bandgap energy ( E g ) tunability, and solution processability.…”
Section: Introductionmentioning
confidence: 99%
“…Photodetectors (PDs) are widely employed in a diverse array of technology platforms including chemical analysis, medicine, environmental monitoring, , defense, , imaging, , space exploration, communications, and the Internet of things. , Recently, metal halide perovskites have attracted massive interest owing to their high optical absorption coefficients of >10 4 cm –1 , long charge carrier lifetimes of >1 μs, diffusion lengths exceeding 1 μm, bandgap energy ( E g ) tunability, and solution processability. Such versatility is also reflected in the vast range of optoelectronic devices they embody such as solar cells, LEDs, lasers, and photocatalysts. The specific detectivity ( D *) is the main figure of merit in PDs. To achieve high D *, the dark current density ( J d ) and consequentially noise current ( i n ) should be reduced.…”
Section: Introductionmentioning
confidence: 99%